Estudio comparativo de cultivares de repollo (Brassica oleracea L. var. capitata L.) para la producción de chucrute: ácidos orgánicos - Goldoni, J.S; Bonassi, I.A. (Instituto Interamericano de Cooperación para la Agricultura (IICA), 2022)
The objective of the present work was to verify organic acids production in a study carded on with 23 cabbage's cultivars, regarding sauerkraut production under natural fermentation Through the obtained results was verified that for all cultivars studied were found acetic, propionic, butyric, valeric, lactic and heptanoic acids. Also iso-butyric acid was found for all cultivars, exception done to Guinshu-YR nc.). 1 cultivar. The levels of these acids varied during the fermentation process, being the amounts of lactic, acetic and heptanoic acids much higher than those of the other ones, from these the lactic acid was predominant. The amounts of iso-butyric and butyric acids were the lowest. The valeric and propionic acids presented intermediary values with predominance of the valeric acid over the propionic acid. Through the determinations of organic acids of low molecular weight it was pos-sible to vertify that all cabbage cultivars resulted in sauerkrauts of good quality.